Local economic development strategy through hiking tourism: A case study of the selo trail on Mount Merbabu - Hasan, Muhammad Aqil (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: The existence of the Selo Hiking Trail tourist attraction also provides job opportunities for the local community to work in various business units. Method: Using Multiplier Effect analysis, this study shows that tourism activities along the Selo Trekking Trail significantly impact the livelihoods of the local community. Economically assessed through Multiplier Effect Analysis, the Keynesian Income Multiplier was found to be 0.6, with a Type I Income Multiplier Ratio of 3.3, and a Type II Income Multiplier Ratio of 3.5, highlighting the substantial economic benefits derived from tourism along the Selo Trekking Route. Result: The study indicates that the high leakage rates, particularly in transportation and logistics costs outside the tourist destination, encourage the development of new business units such as convenience stores or minimarkets, as well as gas stations to meet the needs of tourists. Conclusion: To enhance the broader economic impact of tourism, further research and development are needed, especially in the context of culture-based rural tourism or Community-Based Tourism initiatives. This approach aims to promote sustainable economic benefits while preserving cultural heritage and increasing community participation in tourism activities. Novelty/Originality of this study: This study uses Multiplier Effect Analysis to measure the economic impact of nature tourism and provides quantitative evidence of substantial economic benefits to local communities. The study also identifies new business development opportunities to reduce economic leakage, providing a framework for community-based sustainable tourism development.